THE RELATION OF AL-QUR'ANIC VALUES AND TRADITION: EXPLORING THEOLOGICAL, HUMANIST AND ECOLOGICAL VALUES IN THE DAYAK BEDURUK TRADITION IN SUKA JAYA VILLAGE, SINTANG DISTRICT - Qory Fasdatul Jannah Jannah; Wendi Parwanto; Taufik Akbar; Diaz Ataya Larsen Wijaya (IAT IAIN Pontianak, 2024)
This paper discusses the relationship between Qur’anic values and the Beduruk Tradition in the lives of Dayak people in Suka Jaya Village, Sintang Regency. Beduruk Tradition is a cultural practice that has been passed down from generation to generation and has deep spiritual, social, and ecological values. This study aims to explore the theological, humanist, and ecological values contained in the Beduruk Tradition, as well as to analyze its compatibility with the teachings of the Qur’an. This research uses a qualitative approach with descriptive-analytical method. Data were collected through observation and in-depth interviews with community leaders, RT heads, and local people, as well as through literature studies related to the discussion. The results showed that the Beduruk Tradition contains theological values in the form of expressions of gratitude to God, humanist values in the form of solidarity and helping, and ecological values reflected in respect for nature. These values are in harmony with the teachings of the Qur’an that emphasize monotheism, brotherhood, and human responsibility as khalifah on earth. This finding indicates that Beduruk Tradition not only functions as a cultural heritage, but also has relevance in building harmonious social relations and maintaining the balance of nature. In the context of Muslim society, Beduruk tradition can be practiced as long as it does not contradict Islamic principles. Therefore, preservation efforts are needed with an adaptive approach to Islamic values so that this tradition remains relevant in the modern era. Tulisan ini membahas tentang relasi antara nilai-nilai Al-Qur’an dan Tradisi Beduruk dalam kehidupan masyarakat suku Dayak di Desa Suka Jaya, Kabupaten Sintang. Tradisi Beduruk adalah sebuah praktik budaya yang diwariskan secara turun-temurun, mempunyai nilai spiritual, sosial, dan ekologis yang mendalam. Penelitian ini bertujuan untuk menggali nilai-nilai teologis, humanis, dan ekologis yang terkandung dalam Tradisi Beduruk, serta menganalisis kesesuaiannya dengan ajaran Al-Qur’an. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis. Pengumpulan data dilakukan melalui observasi dan wawancara mendalam dengan tokoh masyarakat, ketua RT, dan masyarakat setempat, serta melalui studi literatur yang berkaitan dengan pembahasan. Hasil penelitian menunjukkan bahwa Tradisi Beduruk mengandung nilai teologis berupa ekspresi rasa syukur kepada Tuhan, nilai humanis dalam bentuk solidaritas dan tolong menolong, serta nilai ekologis yang tercermin dalam rasa hormat terhadap alam. Nilai-nilai tersebut memiliki keselarasan dengan ajaran Al-Qur’an yang menekankan tauhid, persaudaraan, dan tanggung jawab manusia sebagai khalifah di muka bumi. Temuan ini mengindikasikan bahwa Tradisi Beduruk tidak hanya berfungsi sebagai warisan kebudayaan, tetapi juga memiliki relevansi dalam membangun keharmonisan hubungan sosial dan menjaga keseimbangan alam. Dalam konteks masyarakat Muslim, Tradisi Beduruk dapat dilakukan selama tidak bertentangan dengan prinsip-prinsip Islam. Oleh karena itu, diperlukan adanya upaya pelestarian dengan pendekatan yang adaptif terhadap nilai-nilai ke-Islaman agar tradisi ini tetap relevan di era modern.